Problematika Pembelajaran Daring Mata Kuliah Geometri Transformasi di Masa Pandemi Covid-19 - Karsoni Berta Dinata (Eksponen, 2020)
This study aims to analitis the problems of transformation geometry learning at the semester of the 2019/2020 academic year which are carried out online, then attempt to determine solutions and follow-up online learning based on the results of the evaluation. This research is a descriptive qualitative research. The research technique used was a survey technique. The research was carried out on students in semester 4 of the 2019-2020 academic year study program of mathematics education, FKIP Muhammadiyah Kotabumi University in the Transformation Geometry subject with 30 respondents as the object of research. The instrument used was in the form of a questionnaire consisting of 9 questions. The conclusions of this study are 1) it is better if lecturers in online learning use an application that is agreed upon at the beginning of the lecture and is easily accessible to students, 2) it is better if you prepare learning media / materials in the form of digital learning videos that can be accessed via YouTube, WhatsApp, or Instagram. etc., 3) uploading the syllabus, RPS, and material in the learning application, 4) providing lecture information must still be through the learning application and also shared via the WhatsApp Group, 5) providing a grace period for submitting assignments, 6) Continuing to carry out formative and diagnostic assessments for get feedback and return the results of UTS and UAS to Students.